Methods for assessing livestock products competitiveness under economic challenges - Perehuda, Yuliia (Management and Entrepreneurship: Trends of Development, 2024)
The article is devoted to the formation of new scientific solutions regarding the development of methods for assessing Ukrainian livestock product competitiveness in world, international, and national sales markets, considering the impact of economic challenges. It has been emphasized that Ukrainian livestock enterprises have errors in assessing the competitiveness of products (CP) and identifying the strengths and weaknesses of their own competitive position in the world, international, and national sales markets due to the lack of adequate methods of evaluating CP. The article aims to develop a methodology for assessing Ukrainian livestock product competitiveness in world, international, and national sales markets, taking into account the impact of economic challenges. Methodology: a set of general and special methods has been used at the empirical and theoretical levels. It includes historical and comparative assessments to evaluate the competitiveness of Ukrainian livestock products in the world market, comparison – to form requirements for the modern method of assessing livestock products competitiveness of (CLP) on world, international, and national sales markets, taking into account the impact of economic challenges; logical generalization and scientific abstraction – to determine the key components of the methodology recommended for assessing Ukrainian livestock products competitiveness in national, international, and world sales markets; analysis and synthesis – to characterize the group blocks of CLP assessment methodology; methods of systematization, grouping, and logical generalization for information systematization, formation of conclusions and scientific proposals of the article. The article uses system-functional, historical, and systemic approaches to reveal and solve the problems of developing a methodology for assessing Ukrainian livestock product competitiveness in world, international, and national sales markets, taking into account the impact of economic challenges. Results: methods for assessing Ukrainian livestock product competitiveness have been developed, taking into account the impact of economic challenges on the CLP.JEL Classification: О13, Q10